The Influence of Leadership Style, Motivation and Discipline on Employee Performance - Bagus Andrian; Tutik Winarsih (JOURNAL OF MANAGEMENT, ACCOUNTING, GENERAL FINANCE AND INTERNATIONAL ECONOMIC ISSUES, 2025)
This research examines how leadership approaches, employee motivation, and workplace discipline impact worker performance at PT Tigaraksa Satria Tbk Sidoarjo. The study was motivated by recognizing human capital as crucial for organizational success, especially in achieving peak performance through competent leadership, strong motivational drives, and maintained disciplinary standards. The research employed a quantitative methodology with descriptive analysis. The study encompassed the entire workforce of PT Tigaraksa Satria Tbk Sidoarjo, comprising 35 employees, utilizing a complete enumeration sampling approach. Data was gathered through survey questionnaires and personal interviews. The analysis involved testing data validity and reliability, followed by multiple linear regression analysis to examine both combined and individual variable effects. Findings reveal that leadership approaches, motivation levels, and workplace discipline collectively produce significant impacts on worker performance. When examined individually, each factor demonstrates positive performance effects, with employee motivation emerging as the strongest influencing factor. The study concludes that organizations should focus on enhancing leadership quality, strengthening motivational systems, and maintaining disciplinary standards as key strategies for boosting employee performance.